2006
DOI: 10.1159/000093302
|View full text |Cite
|
Sign up to set email alerts
|

Speech Recognition at 1-Year Follow-Up in the Childhood Development after Cochlear Implantation Study: Methods and Preliminary Findings

Abstract: The Childhood Development after Cochlear Implantation (CDaCI) study is a longitudinal multicenter investigation designed to identify factors influencing spoken language in young deaf children with cochlear implants. Normal-hearing peers serve as controls. As part of a comprehensive evaluation battery, a speech recognition hierarchy was designed to assess how well these children recognize speech stimuli across developmental stages. Data were analyzed for the earliest measures in 42 pairs of children reaching 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
1
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 36 publications
9
77
1
6
Order By: Relevance
“…Based on the results of the present study, it is possible that interpretation of these test results may be affected differently by the interaction between age, response context, and informational masking. This complex interplay could be particularly important to consider when response set is manipulated to adjust task difficulty (Eisenberg et al, 2006;Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the present study, it is possible that interpretation of these test results may be affected differently by the interaction between age, response context, and informational masking. This complex interplay could be particularly important to consider when response set is manipulated to adjust task difficulty (Eisenberg et al, 2006;Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Guided by the premise that the functions of hearing and language are interdependent and correlated 2,29,30 , these studies have determined to what extent the skills involved in listening have interfered in The phenomenon "variables involved in speech perception" included studies that evaluated and measured the effects of the independent variablestechnological (such as different speech processors), audiological (use of cochlear implants, type of auditory training), linguistic (such as intonation, tone and speech rhythm) and contextual (silence-noise environments with competition from sound sources) character -in the discrimination and perception of speech sounds for pre and/or post-lingual cochlear implant users. 26,33 Such theme corresponded to 27.9% of the studies and refined the data found regarding the prevalence of research in auditory skills (see Table 1), indicating that speech perception has focused the production of research in the area.Considering that they perceive and behave differentially regarding speech stimuli, it constitutes one of the basic listening skills, investigations that verify all of the variables that affect the perception of this public becomes crucial, in order to offer technological and rehabilitation conditions so that they may acquire it.…”
Section: Analysis By Phenomenamentioning
confidence: 77%
“…This finding, which diverges from other studies in the literature, can be justified by the fact that the children in the present study had a maximum time of device use of six months. Moreover, the auditory abilities assessed through this questionnaire, although considered as initial stages in the process of auditory functioning development, are completely acquired approximately only after one year of device use, represented by a score of 80 to 100% (30) . The results of this study corroborate other findings in the literature in the sense that the redirecting of central structures by means of cochlear implant stimulation can be followed after the period of sensory deprivation through the investigation of CAEP, which proved to be a procedure that can be applied in clinical practice.…”
Section: Discussionmentioning
confidence: 99%